(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The current study aims to identify self-efficacy and its relationship to the level of psychological well-being among female students at the Faculty of Education in the King Abdulaziz University. The sample of the study consisted of (85) female students. The researcher used the descriptive correlative approach. The following scales were used: a measure of self-efficacy- a measure of psychological well-being. The findings showed that there is a significant positive relationship between self-efficacy and psychological well-being in the study sample. Therefore, the study recommends: the need to implement guidance programs to enhance the concept of self -efficacy and psychological well-being among university students, as well as guidance programs to develop academic self -efficacy in students.